Factors affecting academic achievement of undergraduate student in BBA (HONS) human resource management from UiTM Perlis / Syasya Qistina Sharidan - Sharidan, Syasya Qistina
This study was about the factors that affect academic achievement of undergraduate students in BBA (Hons) Human Resource Management form UiTM Perlis. The aim of this study was to determine if the factors such as previous CGPA, family status and academic status affect academic achievement of undergraduate students in BBA (Hons) Human Resource Management from UiTM Perlis. The populations used in this study were students from Faculty Business Management in Bachelor Human Resource Management from UiTM Perlis. Sampling technique used was simple random sampling with a total sample of 173 respondents. The data collection used was through questionnaire. The data from questionnaires had been analyzed using the Statistical Procedure for the Social Science (SPSS) version 21.0. The data analysis techniques that have been used in this study were demographic background, variable analysis, Pearson correlation analysis, multiple regression analysis and hypothesis testing. Based on the research results, it shows that previous CGPA, family status and academic status affect academic achievement of undergraduate students in BBA (Hons) Human Resource Management from UiTM Perlis.